DIGITAL BUSINESS SYSTEMS AS STRATEGIC INFRASTRUCTURE FOR ORGANIZATIONAL SUSTAINABLE DEVELOPMENT - Akulin, Mykhailo; Kotlyk, Andrii; Petrenko, Oleksandr (Current Problems of Sustainable Development, 2026)
The integration of digital business systems into organizational strategy has become essential for achieving sustainable development. Companies face simultaneous pressures to improve operational efficiency, meet environmental, social, and governance goals, and strengthen stakeholder relationships. This paper examines how digital business systems function as strategic infrastructure enabling enterprises to operationalize sustainability practices through systematic measurement, process automation, and real-time optimization. The study synthesizes recent research on digital transformation, sustainable development, and enterprise systems, analyzing the specific contributions of modern ERP and CRM platforms to sustainability management. It proves digital transformation and sustainable development are mutually reinforcing processes creating a “twin transformation” cycle. Modern ERP systems provide four critical capabilities: integrated data architecture eliminating information silos, real-time IoT-based monitoring, automated compliance management, and predictive analytics. CRM platforms complement these by managing external stakeholder relations. A six-step roadmap for implementation is presented. Organizations that integrate digital business systems with sustainability objectives achieve measurable progress across operational efficiency, environmental performance, stakeholder engagement, and governance transparency, establishing durable competitive advantage where technology and sustainability become inseparable elements of coherent enterprise strategy.
Keywords: digital transformation; sustainable development; ERP system; CRM system; ESG performance; twin transformation; competitive advantage